2017
DOI: 10.18203/2320-1770.ijrcog20173475
|View full text |Cite
|
Sign up to set email alerts
|

Third trimester Doppler ultrasound as prediction of obstetric outcome in high-risk pregnancy, Gujarat, India

Abstract: Background: Doppler ultrasound has emerged as beneficial tool in the assessment of the fetal and placental circulation and in the prediction of adverse pregnancy outcome. Umbilical artery Doppler has proved helpful to supervise the growth restricted fetuses and compromised vasculature as in hypertensive disorders high risk pregnancies. Objective of present study was to investigate the association between third-trimester uterine artery Doppler assessment and adverse obstetric outcome.Methods: This prospective s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…This study revealed that, MCA/UA PI and MCA/UAT PI ratio was significantly decreased among preeclamptic than the control group. This agreed with Ghosh et al (21) who found that MCA PI/UA PI ratio was <1, which was statistically significant (p<0.05) in 25.5% and absent in 17.3% among cases of adverse perinatal outcome. Also Shahinaj et al (22) found high sensitivity of the MCA/UA PI ratio in predicting stillbirth (100%).…”
Section: Discussionsupporting
confidence: 92%
“…This study revealed that, MCA/UA PI and MCA/UAT PI ratio was significantly decreased among preeclamptic than the control group. This agreed with Ghosh et al (21) who found that MCA PI/UA PI ratio was <1, which was statistically significant (p<0.05) in 25.5% and absent in 17.3% among cases of adverse perinatal outcome. Also Shahinaj et al (22) found high sensitivity of the MCA/UA PI ratio in predicting stillbirth (100%).…”
Section: Discussionsupporting
confidence: 92%
“…Doppler ultrasound study for fetal circulations would be a useful addition to the obstetrician catalog of tests for antenatal fetal well-being and timely intervention that might be effective in reducing mortality and major morbidity in high-risk pregnancy. 3 increased pulsatility index for veins) to the first-trimester screening. 4 The aim of this study was to evaluate the value of ductus venosus pulstality index of veins in early pregnancy in prediction of adverse pregnancy outcomes.…”
Section: Introductionmentioning
confidence: 99%